NURSE DUTIES IN PANCREATIC SURGERY - Halimova Navbahor Hamdam kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Pancreatitis is the inflammation of the pancreas. The incidence of pancreatitis exceeds 340 patients per million population. Severe pancreatitis, due to the development of pancreatic and peripancreatic necrosis, leads to high morbidity and mortality. Despite many measures taken, severe pancreatitis remains fatal. The limited information on the pathogenesis, outcomes, and treatment uncertainty makes managing severe pancreatitis challenging. Immediate removal of infected or necrotic pancreatic tissue and laparotomy are the gold standard treatments for severe pancreatitis, especially necrosectomy.